PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBASIS RME BERBANTU E-MODUL UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS VIII - Ristiningsih, Ristiningsih; Karimah, Sayyidatul; 'Adna, Syita Fatih (Jurnal Pendidikan Matematika Undiksha, 2021)
The background of this classroom action research is the low ability of mathematics problem solving students in class VIII SMP Cokroaminoto Batang which is caused by the learning model applied which is still teacher-centered, as well as the lack of learning media facilities for students when learning is carried out online. To solve this problem, a classroom action research was carried out through a problem based learning model based on the e-module rocky RME. This research was conducted in 2 cycles. The instruments used in this study were a test instrument for students' mathematical problem solving abilities and teacher activity observation sheets to determine the implementation of learning through problem based learning model based on RME assisted by e-module in mathematics learning. Data collection techniques used in this study were observation and test methods. Furthermore, data from observations and tests were analyzed descriptively quantitatively.The results showed that: (1) The students' mathematical problem solving abilities had increased with students who scored â‰¥ 75 as many as 83.44%; (2) Implementation of learning with a problem based learning model based on RME assisted by e-module with a score of 85.71%.